Comparison between sepsis markers and blood culture in diagnosis of neonatal sepsis: a prospective study - Sonawane, Vijay Baburao; Mehkarkar, Nitin; Gaikwad, Sonali; Kadam, Nitin (International Journal of Research in Medical Sciences, 2017)
Background: Neonatal septicaemia is one of the commonest causes of neonatal mortality and morbidity. Accurate and timely diagnosis of neonatal sepsis remains a major challenge to the pediatricians and neonatologists. In the present study, correlation between sepsis screening and blood culture in neonate presenting with features of sepsis is done to accelerate the diagnostic process and blood culture (considered gold standard) was evaluated as marker for sepsis detection and its effectiveness was compared with other septic markers. Methods: In present study, we emphasize to study early indicators of sepsis screen and their statistical correlation with blood culture (considered as gold standard). Results: As any sepsis screen parameters showed little correlation with blood culture, yet on combination it was found that specificity and positive predictive accuracy increased while sensitivity decreased them individual tests. Also combination of tests yield better results than single tests. Conclusions: The combination of sepsis makers yielded diagnostic results than single tests and proved to be an invaluable aid for early diagnosis of neonatal sepsis.